If the expression is log b(b/x), then the expanded form of the expression looks like 2 log b- log x.
Given that the expression is log b(b/x).
We are required to find the expanded form of the expression.
The change of base formula is basically used to re-write a logarithm operation as a fraction of logarithms with a new base.
We know that log mn= log m +log n and log (m/n)= log m- log n.
The expression is log b(b/x).
We have to first multiply b with the inside fraction.
log b(b/x)=log ([tex]b^{2}[/tex]/x)
(We know that log [tex]a^{b}[/tex]= log b/ log a and log (m/n)= log m- log n)
=log [tex]b^{2}[/tex]- log x
=2 log b - log x
Hence if the expression is log b(b/x), then the expanded form of the expression looks like 2 log b- log x.
Learn more about base change theorem at https://brainly.com/question/14998693
#SPJ4